Prothrombin Time and Activated partial Thromboplastin Time among type 2 none insulin dependent Diabetes Mellitus (T2DM) Patients - Mahdi Hassan, Fathelrahman (Recent Research in Science and Technology, 2009)
Objective: to determine the prothrombin time and activated partial thromboplatin time among type 2 none insulin dependent Diabetes Mellitus Patients. Materials and methods Descriptive, prospective analytical case-control based study conducted in Abdelrahamn Elsedari Hospital, Sakaka city, Aljouf Region, Saudia Arabia during the period of March to July 2009. Fifty patients and ten normal controls were studied. Patients were those who fulfilled the clinical diagnosis of type II none insulin dependent Diabetes Mellitus of either sex in all age groups, on or off treatment. The controls were normal, non- Diabetes Mellitus individuals of either sex. Results The results Show that the mean level of prothrombin time type 2 diabetic patients was 12.0 Sec and of control was 11.1 Sec, it was significantly correlated (P value = 0.02) and the mean level activated partial thromboplastin timeÃ‚Â (APTT) was 30.7 Sec and of control was 31.2 Sec. This result was none significant (P. value = 0.826). Conclusion Our data further demonstrated that patients with type 2 diabetes mellitus had hypercoagulable state and hypofibrinolysis thereby indicating that the activation of coagulation and reduced fibrinolytic activity may contribute to the increased risk of vascular disease in type 2 diabetic patients.